The analysis of slang language in song lyrics in the bruno mars “24k magic album” - Utami, Ni Wayan Lilik Nila; Jendra, Made Iwan Indarwan; Sulatra, I Komang (Institut Pariwisata dan Bisnis Internasional, 2022)
This study entitled The Analysis of Slang Language in Song Lyrics in The Bruno Mars 24K Magic Album. The aim of this study is to find out the types of slang words that are used in song lyrics of Bruno Mars. The analysis concerns with the slang word that occur in song lyric by Bruno Mars on nine song such as 24K Magic, Chunky, Perm, That’s What I Like, Versace on the floor, Straight up & down, Calling all my lovelies, Finesse, Too good to say goodbye. The method being used in this study is a descriptive qualitative method and the technique that is being used in this study is observation technique. The theory used in this analysis is theory by Kipfer and Chapman (2007) to find out the kinds of slang words that occur in song lyrics by Bruno Mars on nine songs. The study concludes that the primary slang word is mostly the secondary slang word on Bruno Mars' song lyrics based on nine songs.